YellowBlack : the first twenty-one years of a poet's life : a memoir - Madhubuti, Haki R., 1942- (Chicago : Third World Press, 2006)
From the Publisher: Powerful prose, poetry, and jazz riffs chronicle the first 21 years of the life of Haki R. Madhubuti, formerly Don L. Lee: poet, publisher, editor, and activist. He was raised by his mother Maxine, whose life is also recounted-including gritty details of how she used her body to feed, house, and shelter her children without help from their absentee father. Despite the obstacles in his childhood, music and literature molded the young Don Lee, effectively saving his life.
Prologue -- Yes -- Part 1: 1942 -- Don Luther Lee -- Jimmy Lee: one -- Little rock -- World as we knew it -- Book -- In our house, there was God -- Fear -- First poet -- Jacklyn Ann -- Maxine and Jimmy Lee -- Roads between -- Detroit -- Jimmy Lee: two -- Street lesson: one -- Maxine -- Jimmy Lee: three -- Don -- Camden, Arkansas -- Grandfather Graves -- Johnny Graves -- Aunt Mayme -- Music -- Libraries -- Books and music -- Used books: finding things of value -- Neighborhood -- Holidays -- Jackie: how can I protect you? -- Life lesson: one -- Makings of a poet -- Aunt sis -- Helen Maxine -- Don: man of the house -- Miss Barmaid of Detroit, 1948 -- Men of God -- Helen Maxine: two -- Janice -- Mable -- Catholic church in our neighborhood -- Friends -- First time -- Women talk -- 1955 -- Helen Maxine: three -- Only love that I knew -- Music and art -- Facing our history was like vinegar on open wounds -- Helen Maxine: the last conversation -- Making transitions -- For Helen Maxine Graves Lee -- Jimmy Lee: a lesson from my father -- Jimmy Lee and Don -- Fathers and priests -- 1960 -- Door to door: the art of language -- Part 2: Making Of Men -- Basic training -- Test of leadership -- I waited -- Learning in the wilderness -- Two opposing armies -- January, 1961-El Paso, Texas -- Last trip to Juarez -- Bloodsmiles -- Part 3: Shaping Thoughts -- Richard Wright -- Paul Robeson -- Re-education of a Negro -- WEB DuBois -- Black art museums -- Ebony museum of Negro history -- Charlie and Margaret Burroughs -- Malcolm X -- Continuing education -- Self-hatred of Don L Lee -- Epilogue.
Keywords: Madhubuti, Haki R., -- 1942- -- Childhood and youth; Poets, American -- 20th century -- Biography; African American poets -- Biography